Improved leptin sensitivity as a potential candidate responsible for the spontaneous food restriction of the Lou/C rat. - Christelle Veyrat-Durebex (Public Library of Science (PLoS), 2013)
The Lou/C rat, an inbred strain of Wistar origin, was described as a model of resistance to age- and diet-induced obesity. Although such a resistance involves many metabolic parameters described in our previous studies, Lou/C rats also exhibit a spontaneous food restriction due to decreased food consumption during the nocturnal period. We then attempted to delineate the leptin sensitivity and mechanisms implicated in this strain, using different protocols of acute central and peripheral leptin administration. A first analysis of the meal patterns revealed that Lou/C rats eat smaller meals, without any change in meal number compared to age-matched Wistar animals. Although the expression of the recognized leptin transporters (leptin receptors and megalin) measured in the choroid plexus was normal in Lou/C rats, the decreased triglyceridemia observed in these animals is compatible with an increased leptin transport across the blood brain barrier. Improved hypothalamic leptin signaling in Lou/C rats was also suggested by the higher pSTAT3/STAT3 (signal transducer and activator of transcription 3) ratio observed following acute peripheral leptin administration, as well as by the lower hypothalamic mRNA expression of the suppressor of cytokine signaling 3 (SOCS3), known to downregulate leptin signaling. To conclude, spontaneous hypophagia of Lou/C rats appears to be related to improved leptin sensitivity. The main mechanism underlying such a phenomenon consists in improved leptin signaling through the Ob-Rb leptin receptor isoform, which seems to consequently lead to overexpression of brain-derived neurotrophic factor (BDNF) and thyrotropin-releasing hormone (TRH).